PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, COACHING LEADERSHIP, DAN DIGITAL LEADERSHIP KEPALA SEKOLAH TERHADAP KOMPETENSI DIGITAL GURU SMP NEGERI DI KABUPATEN PEMALANG - Tohir; Sitti Hartinah DS; Beni Habibi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the influence of transformational leadership, coaching leadership, and digital leadership on teachers' digital competence in Pemalang Regency. The research uses a quantitative approach with a correlational survey method. Data were collected through questionnaires from a sample of 205 teachers and analyzed using multiple linear regression. The results showed that transformational leadership, coaching leadership, and digital leadership have a significant and positive influence on digital competence. This implies that school leadership plays a key role in enhancing teachers' digital skills.